Nepal: a history from the earliest times to the present - Michaels, Axel (Oxford University Press, 2024)
This comprehensive history of Nepal spans pre-historic times and the Licchavi Period to more recent developments, such as the Maoist insurgency and the rise of the republic. In addition to religious history and histories of selected regions (Mustang, Sherpa, Tarai, and others), it covers the nation's relations with its powerful neighbors and its cultural aspects, especially its rich history of arts, architecture, and crafts.
Also issued in print: 2024. - Includes bibliographical references and index. - Description based on online resource and publisher information; title from PDF title page (viewed on January 3, 2024)
Keywords: Nepal -- Social conditions; Nepal -- Civilization; Nepal -- History; Nepal -- Politics and government -- History; Geschichte; Nepal